Nekateri prediktorji življenjskih ciljev v Sloveniji in na Hrvaškem - Poljšak-Škraban, Olga (Psihološka obzorja (Ljubljana), 2008)
Personal goals and interests play an important role in human development because they orient people's life planning, decision-making and also, therefore, their future life course. The article presents the findings of a research which explores the eventual differences between Slovenian and Croatian sample in agency-oriented and communion-oriented life goals and the analysis of significant predictors of above mentioned life goals on both samples. The research included 924 adults of both genders, aged between 21 and 70 years from Slovenia and Croatia. In the study we used the scale of Goals (Pohlman and Brunstein, 1997) and a set of questions regarding various participant's life domains and their perceived importance. The results show significant differences on agency- oriented and communion-oriented life goals between the Slovenian and Croatian sample; in both cases croatian participants reach higher results than those from slovenina sample. As significant predictors in both samples were identified (a) age and importance of effective use of free time for agency-oriented goals, and (b) and gender, parenthood, importance of parenthood and importance of effective use of free time for communion-oriented life goals. The differences in results are explained by respective levels of social modernisation and social welfare, given the fact the Slovenian respondents are embedded in the social environment that offers more possibilities for fullfilment of their life goals, and are closer to postmaterialism and individualism.
Keywords: motivacija; motivation; value; vrednota; starostna razlika; age difference; cultural environment; kulturno okolje; življenjski cilji; vrednote; razvojna psihologija; developmental psychology; starostne razlike; medkulturne razlike; odraslost; Slovenia; Slovenija; Hrvaška; Croatia